2017
DOI: 10.1111/cmi.12790
|View full text |Cite
|
Sign up to set email alerts
|

Novel T3SS effector EseK in Edwardsiella piscicida is chaperoned by EscH and EscS to express virulence

Abstract: Bacterium usually utilises type III secretion systems (T3SS) to deliver effectors directly into host cells with the aids of chaperones. Hence, it is very important to identify bacterial T3SS effectors and chaperones for better understanding of host-pathogen interactions. Edwardsiella piscicida is an invasive enteric bacterium, which infects a wide range of hosts from fish to human. Given E. piscicida encodes a functional T3SS to promote infection, very few T3SS effectors and chaperones have been identified in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 47 publications
1
14
0
Order By: Relevance
“…The finding that the T3SS plays a critical role in the inhibition of endosome maturation and E. piscicida lysosome degradation raised the question of what T3SS effectors are involved in this process. To date, several E. piscicida T3SS effectors including EseG [16], EseJ [17], EseH [18] and EseK [19] have been identified. To assess the role of individual effectors, we tested the ability of WT and isogenic E. piscicida effector mutants to replicate inside non-phagocytic host cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The finding that the T3SS plays a critical role in the inhibition of endosome maturation and E. piscicida lysosome degradation raised the question of what T3SS effectors are involved in this process. To date, several E. piscicida T3SS effectors including EseG [16], EseJ [17], EseH [18] and EseK [19] have been identified. To assess the role of individual effectors, we tested the ability of WT and isogenic E. piscicida effector mutants to replicate inside non-phagocytic host cells.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that T3SS and T6SS mechanisms are essential for the virulence of E. piscicida [15]. An increasing number of T3SS and T6SS effectors have been identified, including EseG [16], EseJ [17], EseH [18], EseK [19] and EvpP [20]. EseG was reported to localize to the ECV membrane, but its function remains undefined [21].…”
Section: Introductionmentioning
confidence: 99%
“…Lentiviral particles were prepared in HEK239T cells as previously described [31]. HT-29 or Caco-2 cells were prepared in approximately 30% density and infected with lentiviral particles containing 10 μg/mL polybrene for 24 h. Transfected cells were selected with puromycin (2 μg/mL).…”
Section: Methodsmentioning
confidence: 99%
“…Very recently, we identified a new E. piscicida T3SS effector, EseK, which can be translocated into host cells with the aid of two chaperones, EscH and EscS. We found that EseK is required for bacterial virulence in zebrafish with unknown mechanisms (24).…”
mentioning
confidence: 99%